Management solutions for internal inspection in high schools in Vietnam: A quality culture approach - Thu, Pham Thuy; Thuy, Le Thi Ngoc (International journal of linguistics, literature and culture, 2025)
This study investigates the management of internal inspection in Vietnamese high schools from the perspective of quality culture. Using a mixed-methods approach, the research surveyed 450 participants, including 250 managers at both provincial and school levels and 200 teachers and staff across six provinces and cities. Twelve public high schools were selected as research sites to represent diverse educational contexts. Data were collected through structured questionnaires and in-depth interviews, then analyzed using SPSS and thematic coding. The findings reveal that while internal inspection is widely institutionalized and contributes to accountability, its alignment with quality culture remains limited. Criteria often emphasize administrative compliance rather than continuous improvement, innovation, or student-centered values. Teachers have limited participation, and transparency and feedback are perceived as insufficient. Leadership quality emerges as a decisive factor, with proactive leaders able to transform inspection into a developmental process. Digital tools are underutilized, further constraining efficiency and transparency. The study proposes five management solutions: (1) raising awareness of managers and teachers about quality culture in inspection, (2) developing criteria aligned with cultural values of quality, (3) standardizing inspection processes based on participatory principles, (4) capacity building for inspection staff, and (5) mobilizing resources and digital platforms for effective implementation.